2020
DOI: 10.26434/chemrxiv.12123204
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In silico identification of widely used and well-tolerated drugs as potential SARS-CoV-2 3C-like protease and viral RNA-dependent RNA polymerase inhibitors for direct use in clinical trials

Abstract: A novel coronavirus (2019-nCoV), officially known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), emerged in China. Despite drastic strict measures, the spread of this virus is ongoing all around the world. SARS-CoV-2 is an agent of coronavirus disease 2019 (COVID-19) characterized by pulmonary infection in humans. There is no vaccine developed against this virus and no approved medication to be used in a treatment yet. In this study, we performed in silico screening against two critical enzym… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 49 publications
0
9
0
2
Order By: Relevance
“…Recent studies on computer‐aided drug screening showed that bromocriptine probably inhibits the SARS‐CoV‐2 replication by exhibiting high binding affinity for both viral RNA‐dependent RNA polymerase and SARS‐CoV‐2 3C‐like protease enzymes 369,370 . Because bromocriptine is widely used clinically as well for a variety of other diseases with high safety profile and cost‐effectiveness, they repurposed it either alone or as an adjuvant with other currently used therapies in the treatment of COVID‐19 371–374 . Moreover, low dose bromocriptine administration has been seen to be fruitful in COVID‐19 patients presenting with NMS and various other central nervous system and endocrine system symptoms 372,375 …”
Section: Pharmacological Significance Of Bromocriptinementioning
confidence: 99%
“…Recent studies on computer‐aided drug screening showed that bromocriptine probably inhibits the SARS‐CoV‐2 replication by exhibiting high binding affinity for both viral RNA‐dependent RNA polymerase and SARS‐CoV‐2 3C‐like protease enzymes 369,370 . Because bromocriptine is widely used clinically as well for a variety of other diseases with high safety profile and cost‐effectiveness, they repurposed it either alone or as an adjuvant with other currently used therapies in the treatment of COVID‐19 371–374 . Moreover, low dose bromocriptine administration has been seen to be fruitful in COVID‐19 patients presenting with NMS and various other central nervous system and endocrine system symptoms 372,375 …”
Section: Pharmacological Significance Of Bromocriptinementioning
confidence: 99%
“…62 https://bi.ahca.myflorida.com/t/ABICC/views/Public/COVIDHospitalizationsCounty?%3AshowAppBanner=fals e&%3Adisplay_count=n&%3AshowVizHome=n&%3Aorigin=viz_share_link&%3AisGuestRedirectFromVizport al=y&%3Aembed=y%20%20%20%20%20#%23%23%23 53 https://www.gov.uk/government/news/spain-removed-from-travel-corridors-exemption-list 54 https://www.nytimes.com/2020/07/25/world/asia/coronavirus-vietnam.html 55 https://www.reuters.com/article/us-health-coronavirus-southkorea/south-korea-reports-113-new-coronaviruscases-most-since-march-idUSKCN24Q01Y 56 https://www.washingtonpost.com/ 57 https://www.reuters.com/article/health-coronavirus-northkorea/north-korea-reports-first-suspected-case-ofcovid-19-kcna-idUSP8N2B8028 58 https://www.theguardian.com/world/2020/jul/27/pet-cat-diagnosed-with-covid-19-uk-government-confirms 59 https://www.foxnews.com/world/china-sees-spike-in-covid-19-cases-6-months-after-who-declares-coronavirusa-health-emergency 60 https://english.elpais.com/society/2020-07-30/spain-records-1153-daily-coronavirus-cases-the-highest-figuresince-may-1.html 61 https://www.reuters.com/article/us-health-coronavirus-airlines-kuwait/kuwait-bans-flights-to-31-high-riskcountries-due-to-coronavirus-idUSKBN24X3QC 62 https://www.bbc.com/news/world-latin-america-53618808 2 Ağustos  Filipinlerde toplam vaka sayısı 100 Bini geçti; vaka sayısı 103 bin 185'e, hayatını kaybedenlerin sayısı ise 2 bin 59'a çıktı. 63 11 Ağustos  Fransa'da Mayıs ayı itibariyle turizm hedefli kısıtlamaların kaldırılmasının ardından bin 397 günlük vaka ile en yüksek sayıya çıkıldığı açıklandı. 64 12 Ağustos  Ürdün artan vakalar nedeniyle Suriye sınırını kapatma kararı aldı.…”
Section: Temmuzunclassified
“…O hal de, Bakan gerçekle uyumlu olmayan bu açıklamayı neden sık sık yapmaktadır?Finansmanı Sağlanacak Sağlık Hizmetlerini Kim Belirlemektedir?Vakıf ve üniversite hastaneleri, Sağlık Bakanlığına bağlı kurum ve kuruluşlar ile özel sağlık kuruluşlarınca üretilen sağlık hizmetlerinin tek kamu "alıcısı" Sosyal Güvenlik Kurumu'dur. Kurum, finansmanı sağlanacak olan sağlık hizmetlerinin kapsamını, bedellerini ve hangi usul ve esaslarla ödeme yapacağını yayımladığı Sağlık Uygulama Tebliği aracılığı ile belirlemektedir (5510 sayılı Kanun Md [63][64][65][66][67][68][69][70][71][72][73]…”
unclassified
“…"Tipranavir", a well-known antiviral protease inhibitor and a known inhibitor of 3CLp of SARS-CoV-2, was used as the reference drug. 12,[36][37][38][39] Computational methods Preparation of receptors and ligands X-ray crystal structure of 3CLp of SARS-CoV-2 (PDB ID 6LU7) was obtained from the protein data bank database. In case of PLp, the homology model of the protein (SMTL ID: 6w9c.1) was obtained from SWISS model database (ESI, SD-2 †).…”
Section: Introductionmentioning
confidence: 99%